2021
DOI: 10.5606/tftrd.2021.6415
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia in ankylosing spondylitis

Abstract: Objectives: This study aims to determine the effect of ankylosing spondylitis (AS) on alexithymia. Patients and methods: In this study, a total of 55 AS patients (30 males, 25 females; mean age: 40±8 years; range, 21 to 57 years) who were under follow-up and 55 age- and sex-matched healthy volunteers (31 males, 24 females; mean age: 38.9±8.5 years; range, 21 to 53 years) were included between March 2016 and August 2016. Toronto Alexithymia Scale (TAS), and Beck Depression Inventory (BDI) were performed to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 34 publications
(35 reference statements)
1
9
1
Order By: Relevance
“…Another study on AS patients reported that AS patients had a higher rate of alexithymia than controls, and alexithymia was more common in women than in men. They also stated a weak correlation between the disease activity scale BASDAI and the DIF subscale 17 . In our study, being female was associated with a 22 times increased risk of alexithymia compared with males in the multivariable analysis.…”
Section: Discussioncontrasting
confidence: 46%
See 3 more Smart Citations
“…Another study on AS patients reported that AS patients had a higher rate of alexithymia than controls, and alexithymia was more common in women than in men. They also stated a weak correlation between the disease activity scale BASDAI and the DIF subscale 17 . In our study, being female was associated with a 22 times increased risk of alexithymia compared with males in the multivariable analysis.…”
Section: Discussioncontrasting
confidence: 46%
“…In addition, old age, low education level, male gender, and low socioeconomic conditions are reported as being associated with an increase in alexithymia 15 . Importantly, alexithymia and other psychological problems, such as depression, anxiety, and impulsivity, are remarkably widespread in axSpA patients and may negatively influence their quality of life and lower compliance with treatment 11,16–18 . Coexisting pain, alexithymia, depression, and inflammation were investigated in patients with chronic pain conditions, including temporomandibular joint disorders, chronic migraine, complex regional pain syndrome, and low back pain, as well as rheumatic diseases 19,20 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another relevant factor that has been shown to negatively influence the extent of depressive symptoms and which seems to share the inflammatory pattern and the correlation with various chronic inflammatory diseases, is represented by alexithymia, the difficulty in identifying, recognizing, distinguish, and express the own and others feelings [ 61 , 62 , 63 , 64 ]. Similarly, with specific regard to alexithymia, recent studies highlighted a pathogenetic correlation with specific inflammatory markers such as TNF-α and IL-6 exists [ 36 , 37 , 38 , 65 , 66 , 67 ].…”
Section: Correlation Between Depression and Other Psychopathological ...mentioning
confidence: 99%